Renal dysfunction as intrahospital prognostic indicator in acute pulmonary embolism. (1st March 2020) - Salinger-Martinovic, Sonja; Dimitrijevic, Zorica; Stanojevic, Dragana; Momčilović, Stefan; Kostic, Tomislav; Koracevic, Goran; Subotic, Bojana; Dzudovic, Boris; Stefanovic, Branislav; Matijasevic, Jovan; Miric, Milica; Markovic-Nikolic, Natasa; et al.
Abstract: Background: Acute pulmonary embolism (PE), due to hemodynamic disturbances, may lead to multi-organ damage, including acute renal dysfunction. The aim of our study was to investigate the predictive role of renal dysfunction at admission regarding the short-term mortality and bleeding risk in hospitalized PE patients. Methods: The retrospective cohort study included 1330 consecutive patients with PE. The glomerular filtration rate (GFR) was calculated using the serum creatinine value and Cocroft-Gault formula, at hospital admission. Primary outcomes were all-cause mortality and PE-related mortality in the 30 days following admission, as well as major bleeding events. Results: Based on the estimated GFR, patients were divided into three groups: the first with GFR < 30 mL/min, the second with GFR 30–60 mL/min, and the third group with GFR > 60 mL/min. A multivariable analysis showed that GFR at admission was strongly associated with all-cause death, as well as with death due to PE. Patients in the first and second group had a significantly higher risk of 30-day all-cause mortality (HR 7.109, 95% CI 4.243–11.911, p < 0.001; HR 2.554, 95% CI 1.598–4.081, p < 0.001). Fatal bleeding was recorded in 1.6%, 0.5% and 0.8% of patients in the first, second and in the third group ( p < 0.05). There were no significant differences regarding major bleeding rates among the groups. Conclusion: Renal dysfunction at admission in patients with acute pulmonary embolism is strongly associated with overall PE mortality. Highlights: Glomerular filtration rate has a predictive role in pulmonary embolism. Patients with pulmonary embolism and renal dysfunction have poor prognosis. Renal dysfunction is associated with higher bleeding rates in pulmonary embolism.